The conceptual relationship between green supplier development and organizational performance - Abdul Hamid, Abu Bakar (2013)
Green supplier development is the key coordinate of economic and social development that will contribute to the achievement of green supply chain management and therefore improving supply chain competitive advantage and organizational performance. By reviewing and analyzing many previous supplier development programs which were collected from supplier development and green supply chain management literature, three supplier development programs related to both economic and environmental performance are summarized in this study including green knowledge transfer and communication, investment and resource transfer, and management and organizational practices. This paper aims to provide a conceptual support to future empirical investigation of the relationship between green supplier development and organizational performance.